Furosemide in the Treatment of Phosgene Induced Acute Lung Injury. Issue 4 (1st December 2010) - Grainge, C; Smith, Adam; Jugg, BJ; Fairhall, SJ; Mann, T; Perrott, R; Jenner, J; Millar, T; Rice, P
Abstract : Method: Using previously validated methods, 16 anaesthetised large white pigs were exposed to phosgene (target inhaled dose 0.3 mg kg -1 ), established on mechanical ventilation and randomised to treatment with either nebulised furosemide (4 ml of 10 mg.ml -1 solution) or saline control. Treatments were given at 1, 3, 5, 7, 9, 12, 16 and 20 hours post phosgene exposure; the animals were monitored to 24 hours following phosgene exposure. Results: Furosemide treatment had no effect on survival, and had a deleterious effect on PaO2 : FiO2 ratio between 19 and 24 hours. All other measures investigated were unaffected by treatment. Conclusion: Nebulised furosemide treatment following phosgene induced acute lung injury does not improve survival and worsens PaO2 : FiO2 ratio. Nebulised furosemide should be avoided following phosgene exposure.